2005
DOI: 10.2325/jbcs.12.196
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bilateral breast cancer on the prognosis of breast cancer: a comparative study with unilateral breast cancer

Abstract: Our data suggest that metachronous bilateral breast cancer is associated with shorter disease-free survival than synchronous bilateral or unilateral breast cancer, although overall survival does not differ among the 3 groups. Patients with metachronous bilateral breast cancer should be followed particularly closely in order to detect recurrence early and maximize quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
37
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 18 publications
5
37
0
5
Order By: Relevance
“…As our study does not include unilateral patient data, the median age comparison cannot be made with the BBC, it is compatible with the literature data. In above studies where BBC and UBC case ages are compared, statistically significant difference in ages of both groups have not seen (Takahashi et al, 2005;Vuoto et al, 2010;Kheirelseid et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…As our study does not include unilateral patient data, the median age comparison cannot be made with the BBC, it is compatible with the literature data. In above studies where BBC and UBC case ages are compared, statistically significant difference in ages of both groups have not seen (Takahashi et al, 2005;Vuoto et al, 2010;Kheirelseid et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…When compared with UBC historical data (70-80% IDC), the histopathology is similar in BBC patients (SC 81% and 76%; MC 70% and 76%; p=0.9) (Beckmann et al, 2001;Takahashi et al, 2005;Verkooijen et al, 2007;Vuoto et al, 2010 ). In a study comparing BBC and UBC the IDC ratio was reported as 66% (SC) and 63% (MC), respectively (Verkooijen et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Surgery [14,15,25,29,36] and CA 15-3 marker [15] are the other factors that can be considered in the survival analysis. Furthermore, the combination of the following factors have been suggested across different studies: familial history [24], smoking [24], affected side [20,39], place of residence [29], number of involved lymph nodes [22,24,27,31,34,35,37], stage [5,6,8,17,25,26,42], stage of surgery [25], tumor size [16, 19, 20-24, 27, 28, 31, 34, 35, 37, 38, 41], complete clinical and pathological response [41], medicine [29], type of pathology [32], type of treatment [17,21], chemotherapy [25,33,36,37], neoadjuvant chemotherapy [18], radiotherapy [25,33,36], number of metastasis [30], bone pain [30], and time interval leading to bone metastasis [42]. No study has considered chronic diseases as an effective factor of survival analysis.…”
mentioning
confidence: 99%
“…Metastasis [4,6,14,16,28,42], background of benign tumors [4], and age at diagnosis [4,5,16,INTRODUCTION 22,23,24,25,26,28,29,[32][33][34][35][36][37]39] were considered as the main factors in the survival analysis. Some studies emphasized on the factors such as hormone therapy (hormone receptor) [9,12,16,20,22,23,25,27,33,35,36,38], Her2 [9,11], grade [9,11,13,19,21,24,31,34,37,38], and lymph node involvement [11,19,…”
mentioning
confidence: 99%